ANALISIS PENERAPAN GREEN MARKETING DAN LIFE STYLE TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE BODY SHOP DI KOTA KEDIRI - Pangastuti, Ria Lestari (Jurnal Manajemen dan Profesional, 2024)
The purpose of this study is to determine whether green marketing and lifestyle influence the purchasing decision of The Body Shop products partially and simultaneously. The population of this study was all customers of The Body Shop in the city of Kediri. The technique used for sampling used the probability sampling technique, namely purposive sampling. The data collection method was an offline questionnaire. The proposed hypothesis was tested using multiple regression analysis techniques. The results of this study are that Green marketing has a positive and significant effect on purchasing decisions of The Body Shop products, Life Style has a positive and significant effect on decisions of The Body Shop products, Green marketing and lifestyle together have a positive and significant effect on purchasing decisions of The Body Shop products.